Exchange flow in a highly stratified fjord in drought conditions - Pinilla, Elias; Ross, Lauren; Pérez-Santos, Iván (Frontiers in Marine Science, 2024)
Fjords are known for their biodiversity and abundant aquaculture resources. However, climate and anthropogenic pressures are altering fjord biological, physical, and chemical processes that will undoubtedly change the ecosystem as a whole. To investigate the impact of climate change on fjord functioning, this study examines the impacts of drought conditions on the physical dynamics and salinity variations in a fjord known for its bolstering aquaculture industry in Northern Chilean Patagonia, the Reloncaví Fjord (41.5° S). Using a high-resolution hydrodynamic model and the Total Exchange Flow (TEF) framework, we analyzed the impacts of river discharge, tides, and wind during a dry year (2016) and a typical year (2018). In 2016, reduced freshwater input decreased exchange flow and increased salinity compared to 2018. In 2018, river discharge dominated TEF variability (74%), while tides and wind contributed 17% and 9%, respectively. In summer 2016, tidal and wind influences rose to 21% and 16%, highlighting their role under low freshwater conditions. Increased wind facilitated destratification, mixing high-salinity subsurface waters with fresh surface layers, affecting ecosystem dynamics. From these results we developed a method to predict long-term stratification variability (1980–2021), identifying critical ecological shifts. Logistic regression models showed significant links between stratification levels and harmful algal blooms (HABs) of Pseudchatonella spp. and Alexandrium catenella. Lower stratification was linked to higher Pseudchatonella spp. HABs in summer, while higher stratification correlated with Alexandrium catenella blooms in spring, tied to increased river discharge. These results suggest that severe HAB events in Northern Patagonia may become more frequent with climate change, underscoring the need to consider local environmental dynamics and stratification in HAB studies.